Low-wage employment in Europe - Bazen, S (Elgar; distributed by American International Distribution Corporation, Williston, Vt, 1998)
Eight papers, originally presented at a conference held at the Universite Montesquieu Bordeaux IV and organized as part of the activities of the Low-wage Employment Research (LoWER) network financed by the European Union, explore the problems of low-wage employment in Europe. Papers focus on comparisons of low-paid employment in France, Great Britain, and the Netherlands; the incidence and evolution of low-wage employment in the Netherlands and the United States, 1979-89; a fourteen-country comparative analysis of the link between low pay and poverty; low pay, the earnings distribution, and poverty in Ireland, 1987-94; atypical work as a form of low-wage employment in the German labor market; evidence from Spain on the effects of minimum wages; evidence from French panel data on sub-minimum-wage employment, earnings profiles, and wage mobility in the low-skill youth labor market; and low wages of school-leavers of vocational education in the Netherlands. Bazen is at the Universite Montesquieu, Bordeaux. Gregory is at St. Hilda's College, Oxford University. Salverda is at the University of Groningen. Index.